The application of foreign law in the British and German courts - Critchley, Alexander DJ (London : Hart Publishing, 2022)
This book explores the application of foreign law in civil proceedings in the British and German courts. It focuses on how domestic procedural law impacts on the application of choice of law rules in domestic courts. The work comparatively engages with the questions of procedure, determination and investigation as they affect the law in England and Wales, Scotland, and Germany. Although the relevant jurisdictions are the focus, the comparative analysis extends to explore examples from other jurisdictions, including relevant international and European conventions. Ambitious in scope, it expertly tracks the development of the question and looks at possible future reforms..
1. Fundamentals --2. Historical --3. Current --4. Future.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Law -- Legal profession -- Scotland; Legislation; Private law